Foldable Tennis Ball Picker - Mohd Fadhil, Muhammad Adam Haris; Badrun, Rasyidi; Jamaludin, Muhammad Izzad Asyraf Jamaludin; Janon, Mohd Najib; Mohammad Noor, Hafsa; Tuan Ibrahim, Tuan Mohd Hafeez (Multidisciplinary Applied Research and Innovation, 2026)
During tennis training sessions, large numbers of balls are dispersed and must be retrieved quickly to maximize practice efficiency; however, existing retrieval tools are often either manually operated and physically demanding or mechanically powered, bulky, and non-portable. To address these challenges, a Foldable Tennis Ball Picker was designed and developed for individual players and training facilities using a systematic product design process that translated user needs into product specifications and screened alternative designs via a weighted rating method. Performance testing revealed that the prototype consistently outperformed manual collection, achieving an average retrieval time of 7.58 seconds and providing an average time saving of 2.26 seconds per test. The device features a ball storage compartment with a 70-ball capacity and an integrated folding mechanism that reduces storage volume by more than 50%. Structural durability was confirmed by rolling the picker over court surfaces more than 500 times, during which the aluminum frame and joints remained secure and perfectly aligned. Collectively, these results demonstrate that the foldable ball picker successfully supports efficient retrieval, minimizes physical strain, and offers a compact, cost-effective solution suitable for various tennis training contexts.